The Effects of Antenna Position on RF Exposed Human Head - (:unkn) unknown (IEEE, 2016)
The aim of this paper is to examine the effects of antenna position at different angles by measuring the specific absorption rate (SAR) using finite element method (FEM) in a human head (SAM Model). This model is created in COMSOL Multiphysics. In this study, a patch antenna is placed at the side of the head model at different angle positions. SAR and temperature increase simualtions are performed.
Keywords: electromagnetic propagation; finite element method; human head; specific absorption rate; temperature increase